How Can Copilot Assist in Creating Accessible Websites? An Empirical Study - Teran, Luciano A.; da Rocha, Thayssa A.; da Silva, Ingrid M. M.; de Salles, Rafael B.; Melo, Giselle L. N.; Mota, Marcelle P.; de Souza, Cleidson R. B. (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2025: Anais do XXIV Simpósio Brasileiro sobre Fatores Humanos em Sistemas ComputacionaisDO - 10.5753/ihc.2025.10811, 2025)
Introduction: Software developers have used intelligent coding assistants to aid their development efforts. Objective: We investigated GitHub Copilot’s support for creating accessible software applications. We explored its capacity to generate code suggestions that adhere to accessibility best practices during the development of a web application. Methodology: We analyzed the results using an inspection tool and the content of development diaries. Results: Our results indicate that the assistant provides limited accessibility support, exhibiting three distinct behaviors: in some cases, it generates code that adheres to accessibility criteria autonomously, while in others, it requires detailed prompting. Furthermore, in some cases, it does not even provide accessibility support when explicitly requested by the developer.